Peran Kantor Perwakilan Bank Indonesia Provinsi Sumatera Utara Dalam Meningkatkan Pasar Keuangan Syariah - Isra Hayati; Siti Fatimah; Saparuddin Siregar (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2020)
The purpose of this study was to find out about the role of the Bank Indonesia North Sumatra Province representative office in improving the Islamic financial market. The research approach used is a qualitative approach. Data collection techniques and tools used are interviews and observation. The data analysis technique used is descriptive data analysis technique. Based on the results of the study, the authors draw the conclusion that the development of Islamic financial markets has increased from 2017. Bank Indonesia has a prudential macro policy, namely the policy on Financial System Stability. Where, the policy is able to control the risks that exist in the development of Islamic financial markets.            Keywords: Financial System Stability and Islamic Financial Market